Answering Islamic Questions with a Chatbot using Fuzzy String-Matching Algorithm - Sihotang, M T; Jaya, I; Hizriadi, A; Hardi, S M (Journal of physics. Conference series, 2020)
The guidance of Muslims in worship refers to the holy Quran and the hadith. Not all people understand the law related to a case in accordance with Islamic teachings. Questions relating to a matter based on Islamic law are widely circulated on the Internet with long and detailed answers. This is good but for some people, a short and direct answer to the core is the desired answer, of course in accordance with the majority of Muslim scholars. One of the many technologies that can be used to answer questions is chatbot. A chatbot is one of many implementations of Natural Language Preprocessing. In this study, the chatbot can find answers to questions in accordance with Islamic law using the fuzzy string-matching algorithm. The research test data were obtained from several people who used chatbot directly by looking at pairs of questions and answers whether they were appropriate or not. The accuracy of the test is 70.37% and the chatbot's performance is quite good.